Hubungan Asupan Zat Besi (Fe) dan Protein dengan Kejadian Anemia pada Ibu Hamil - Nadia Sagita; Asep Jalaludin Saleh; Radella Hervidea (Jurnal Kebidanan dan Keperawatan Medika, 2026)
Anemia in pregnant women is a major public health problem in Indonesia, including in Bandar Lampung, with a high prevalence. One of the main causes of anemia is inadequate nutritional intake, particularly iron and protein. Insufficient protein intake can disrupt iron transport for hemoglobin synthesis, increasing the risk of anemia. This study aimed to determine the relationship between iron and protein intake and the incidence of anemia in pregnant women at Gedong Air Public Health Center, Bandar Lampung, in 2025. This study used a cross-sectional design with a population of 257 pregnant women and a sample of 80 respondents selected through accidental sampling. Data on anemia incidence were obtained from the Public Health Center, while iron and protein intake data were collected through 3x24-hour food recall interviews and analyzed using Nutrisurvey software. Data were analyzed using univariate and bivariate methods with the chi-square test at a 95% confidence level. The results showed that 60.0% of respondents experienced anemia, 88.8% had insufficient iron intake, and 80% had insufficient protein intake. The chi-square test showed no significant relationship between iron intake and anemia incidence (p=0.773), as well as no significant relationship between protein intake and anemia incidence (p=0.732). Although statistically insignificant, this study indicates that anemia prevalence among pregnant women in this area remains high, with most respondents having inadequate iron and protein intake. Adequate fulfillment of iron and protein remains crucial to prevent anemia and pregnancy complications.